Waterbirds Diversity in Bengawan Solo Estuary, Gresik, East Java - Hani Sabrina; Ani Mardiastuti; Jarwadi Budi Hernowo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Bengawan Solo Estuary has a very large area of mudflat, which make it suitable area for waterbird’s habitat. The purpose of this study were to determine the value of diversity index of waterbirds. This study was conducted in mudflat area at Kali anyar estuary, Bengawan Solo. Data was collected on March 2018. The method used to calculate the waterbirds was concentration count and to estimate the population was used block method. The result showed that value of diversity index of birds was 2,029 with the value index of evenness was 0,553. Total species found were 39 species from 7 families. Calidris canutus, Calidris tenuirostris, Chlidonias hybridus and Chlidonias leucopterus were dominant species. There were 2 species Endagered and, 7 spesies Near Threatened according to IUCN also Tweleve spcies were protected in Indonesia. Keywords: Bengawan Solo, bird diversity, mudflat, waterbirds